2021
DOI: 10.1136/fmch-2021-000919
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric primary care in Germany during the early COVID-19 pandemic: the calm before the storm

Abstract: ObjectivesGlobally, the COVID-19 pandemic has a major impact on healthcare provision. The effects in primary care are understudied. This study aimed to explore changes in consultation numbers and patient management during the COVID-19 pandemic, and to identify challenges for patient care.DesignSurvey of paediatric primary care practices on consultation numbers and patient management changes, and semistructured interviews to identify challenges for patient care. Surveys and interviews were partially linked in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
3
3
1
Order By: Relevance
“…A key finding within the first theme was that providers witnessed the heightened role of SES in mitigating or exacerbating the effects of the pandemic on youth with chronic pain. This finding aligns with previous work reporting a contrast in the care received by patients of varying SES during the pandemic [ 24 ]. In a German study, Vasconcelos et al found that pediatric patients with chronic conditions and those who were socio-economically disadvantaged were more likely to be reported as receiving worse care during the pandemic, in comparison to those with minor concerns who were more likely to be reported as receiving better care [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A key finding within the first theme was that providers witnessed the heightened role of SES in mitigating or exacerbating the effects of the pandemic on youth with chronic pain. This finding aligns with previous work reporting a contrast in the care received by patients of varying SES during the pandemic [ 24 ]. In a German study, Vasconcelos et al found that pediatric patients with chronic conditions and those who were socio-economically disadvantaged were more likely to be reported as receiving worse care during the pandemic, in comparison to those with minor concerns who were more likely to be reported as receiving better care [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding aligns with previous work reporting a contrast in the care received by patients of varying SES during the pandemic [ 24 ]. In a German study, Vasconcelos et al found that pediatric patients with chronic conditions and those who were socio-economically disadvantaged were more likely to be reported as receiving worse care during the pandemic, in comparison to those with minor concerns who were more likely to be reported as receiving better care [ 24 ]. A qualitative study of adults with chronic pain also reported that existing systemic inequities intermingled with the existence of chronic health conditions lead to worse health outcomes and more precarious financial positions [ 22 ] for adults of lower SES [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Whereas patients with symptoms suggesting a COVID-19 infection had been advised not to visit medical practices in person, many patients with other serious symptoms were also afraid to visit their doctor, or did not attend preventive medical check-ups for fear of becoming infected with COVID-19 ( 25 , 26 ). In pediatric practices emergency visits were significantly reduced, whereas developmental examinations remained mostly unchanged, compared to the previous year ( 27 ). Studies show, that vaccination uptake was affected during the pandemic, however could be resumed ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 94%